2022
DOI: 10.3390/nu14142993
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Characteristics of People with Obesity by Meta-Analysis of Existing Datasets

Abstract: Obesity is a complex chronic, relapsing, progressive disease. Association studies have linked microbiome alterations with obesity and overweight. However, the results are not always consistent. An integrated analysis of 4282 fecal samples (2236 control (normal weight) group, 1152 overweight, and 894 simple obesity) was performed to identify obesity-associated microbial markers. Based on a random effects model and a fixed effects model, we calculated the odds ratios of the metrics, including bacterial alpha-div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 53 publications
1
18
0
2
Order By: Relevance
“…Fecal microbiota transplantation (FMT) is a novel treatment method which is to transfer the functional microbiota from normal feces to an unbalanced gastrointestinal tract, reconstruct a new intestinal flora, and resume the host function ( Costello et al., 2017 ; Liu et al., 2021 ) This technique has proven effective impact in many microbiota-related metabolic ( Lee et al., 2019 ; Que et al., 2021 ; Gong et al., 2022 ), infectious ( Smillie et al., 2018 ), and inflammatory diseases ( Weingarden and Vaughn, 2017 ; Zhang et al., 2019 ). In recent research, the patients have recurrent Clostridium difficile infection were extremely effective treated by FMT (about 90% cure rate) ( Le Bastard et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) is a novel treatment method which is to transfer the functional microbiota from normal feces to an unbalanced gastrointestinal tract, reconstruct a new intestinal flora, and resume the host function ( Costello et al., 2017 ; Liu et al., 2021 ) This technique has proven effective impact in many microbiota-related metabolic ( Lee et al., 2019 ; Que et al., 2021 ; Gong et al., 2022 ), infectious ( Smillie et al., 2018 ), and inflammatory diseases ( Weingarden and Vaughn, 2017 ; Zhang et al., 2019 ). In recent research, the patients have recurrent Clostridium difficile infection were extremely effective treated by FMT (about 90% cure rate) ( Le Bastard et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported that Butyricimonas could prevent high fat diet-induced diabetes and metabolic disorders in mice via the GLP-1 receptor [ 62 ]. Butyricimonas has also been negatively correlated with insulin resistance and obesity in humans [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The family Ruminococcaceae and the genus Ruminococcus are involved in alcohol metabolism [39] , adipokine metabolism [40] , cirrhosis [41] , acute-on-chronic liver failure [42] , allergy [43,44] , antibiotic biosynthesis [45] , in ammation [46] , and cardiovascular risk [47] . However, the involvement of these bacteria in BW changes is controversial, with reports stating that individuals with obesity have increased [48][49][50] or decreased [51][52][53] abundance of Ruminococcaceae or that it varies with species [54] . As for the mechanism by which Ruminococcaceae members are involved in host BW regulation, it has been suggested that they degrade various polysaccharides to produce short-chain fatty acids (SCFAs) [55] .…”
Section: Discussionmentioning
confidence: 99%